X-ray imaging : fundamentals, industrial techniques, and applications /: fundamentals, industrial techniques, and applications. (2016) - Martz, Harry E, 1957-; Logan, Clint M, 1941-; Schneberk, Daniel J, 1942-; Shull, Peter J, 1957-
No abstract available